Deficient representation of bamboos woven motifs and patterns in Malay architecture - Idris, Mariam; Md Hashim, Azhari; Abdullah, Fadilah (Universiti Teknologi MARA, Kelantan, 2018)
Home is the first place where the message of Islam was spread or where Islamic teaching was practiced. Its construction is in accordance with Islamic law. Residents are also educated with Islamic values. Inside the house, there are decorations to beautify the home. Indeed, God does not prevent his servants to decorate the house as long as the source obtained is good and lawful. The present research employs qualitative research encompasses the concept of descriptive design. The techniques denote a documental photography including the materials in its surrounding. The latter focused upon possible differences in types of motifs and patterns of bamboos woven in Malay architecture through design arrangement and weaving composition. The research indicated the Islamic art in visualize of bamboos woven motifs and patterns used on roof, walls, doors, and windows of Malay architecture. It clearly describes the deficient representational of visual depicted from nature through the usage of bamboo. This research nurtures awareness among community in appreciating the Malay‟s architectural heritage. In the teaching of Islam, something that is appreciated must be things that are good, noble, beautiful, true, meaningful and useful. Indeed, enjoying literary art is not merely for appreciation, but it adds to the belief in God. This is because a sense of pleasure and gratitude can learn the truth of art. Hence, it built positive effects in the level of mind and heart. Positive mind and heart will build the power of faith. As a result, an educated will be born society with manners and acknowledges the oneness in God in their world affairs.